1996
DOI: 10.2307/3432760
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A 2 Is Involved in the Mechanism of Activation of Neutrophils by Polychlorinated Biphenyls

Abstract: Aroclor 1242, a mixture of polychlorinated biphenyls (PCBs), activates neutrophils to produce superoxide anion (O2-) by a mechanism that involves phospholipase C-dependent hydrolysis of membrane phosphoinositides; however, subsequent signal transduction mechanisms are unknown. We undertook this study to determine whether phospholipase A2-dependent release of arachidonic acid is involved in PCB-induced O2- production. We measured O2- production in vitro in glycogen-elicited, rat neutrophils in the presence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…7 PLA 2 are shown to be involved in the mechanism of activation of neutrophils by polychlorinated biphenyls. 8 In conclusion, our results indicate that Ca 2+ activation of PLA 2 is involved in the TMCH-induced activation of respiratory burst. The consequence is a rapid activation of the general immune system and unessecary production of free radicals that can be harmful to the tissue.…”
Section: Discussionsupporting
confidence: 51%
“…7 PLA 2 are shown to be involved in the mechanism of activation of neutrophils by polychlorinated biphenyls. 8 In conclusion, our results indicate that Ca 2+ activation of PLA 2 is involved in the TMCH-induced activation of respiratory burst. The consequence is a rapid activation of the general immune system and unessecary production of free radicals that can be harmful to the tissue.…”
Section: Discussionsupporting
confidence: 51%
“…This gene encodes cytosolic phospholipase A 2 -α (cPLA 2 -α) playing a central role in the release of arachidonic acid (AA) from sn2 position of membrane phospholipids, and AA metabolism is involved in a number of biological events such as inflammatory and carcinogenic processes. Previous studies revealed that TCDD promoted the release of AA from membranes as a result of its ability to stimulate membrane lipid oxidation and phospholipase A 2 (PLA 2 ) activity (al-Bayati and Stohs, 1991;Forsell et al, 2005;Tithof et al, 1996Tithof et al, , 2002. Therefore, our finding might fill-in the missing link between TCDD stimulation and phospholipase A 2 induction.…”
Section: Discussionmentioning
confidence: 75%
“…PCB exposure is also associated with a modest decrease in maternal and umbilical cord serum arachidonic acid concentrations [37]. Several reports describe cellular activation by PCBs as well as induction of arachidonic acid release from different mammalian cells including rat neutrophils, myometrial cells and neuronal cells [38][39][40][41][42][43][44]. In neuronal cell culture model, PCBs induce arachidonic acid release and perturbed intracellular signaling [43,45], suggesting a possible link between arachidonic acid metabolism and neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%